Perceptions of Takmir and Congregants of the Ar-Rahmah Mosque in Situbondo Regarding the Implementation of the Covid19 Prevention Protocol in the New Normal Era - Imansyah, Achmad Ghifari (al-Hikmah : Jurnal Studi Islam, 2021)
In 2020 the world has been shaken by the arrival of the Covid-19 pandemic outbreak. This pandemic has spread to various parts of the world so that it requires all parties to implement the existing Health protocols. However, these protocols are interpreted and treated differently in the Ar-Rahmah Mosque environment. This research is aimed at finding out how the perception of the takmir and the congregation of the Ar-Rahmah Mosque so that it affects the implementation of the Covid-19 prevention protocols so that they are not carried out according to existing procedures. The research method used by the researcher is descriptive and qualitative methods, with data collection through interviews with Takmir and the Ar-Rahmah Mosque congregation. The findings of this study indicate that this perception arises due to a lack of information and further counseling for the Takmir and congregation of the Ar Rahmah Mosque, so that it is less than optimal in carrying out protocols to prevent the spread of Covid19. This study also found that the dissemination of further information to takmir and congregants should be the initial step in improving the perception of the Ar-Rahmah Mosque Congregation towards Health protocols in the new normal era so that their implementation is hampered properly and is able to run smoothly.